AUDIOVISUAL AND SONG TRANSLATION OF INDONESIAN SUBTITLE IN SHELTER MUSIC VIDEO - Mohamad Irham Poluwa; Nafilaturif'ah Nafilaturif'ah (Universitas Islam Sumatera Utara (UISU), 2021)
The current study aimed to find out the translation techniques applied by the translator in creating the Indonesian subtitles for the original lyrics of Shelter – a collaboration project of music video by Porter Robinson and Madeon, A1-Pictures and Crunchyroll uploaded on YouTube in 2016. The data were analyzed based on the audiovisual translation theory, especially the linguistics of subtitling, the translation technical procedures in the compared stylistics, and the choice in song translation. The study also applied qualitative approach which enabled the researchers to emerge data in descriptive way (in the form of words or pictures instead of numbers). Furthermore, the data were also in the forms of an audiovisual content. The study indicated that most of the lyrics were translated based on literal translation that was reflected by the equivalence of the source language and the target language. The audiovisual theory, particularly reduction theory was also applied in creating the subtitles. In addition, the subtitles were created without taking the music into consideration, meaning that the subtitles were devoted as a supplement or no more than another piece of the source text.